2016
DOI: 10.14710/jpki.11.1.51-65
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kasus Kecelakaan Kerja pada Pekerja Pengeboran Migas Seismic Survey PT. X di Papua Barat

Abstract: Oil and gas industry is one of the industries with the level of risk of accidents is very high. Workplace accidents are generally caused by two main points, namely the behavior of unsafe working (unsafe act) and unsafe working conditions (unsafe conditions). The research objective is to analyze the actions and unsafe environment with workplace accidents in PT. X. This study was conducted analytic observational case control design. Number of samples 60 people, including 30 cases (Workers injured at work) and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
3
3
0
10
Order By: Relevance
“…In addition, a study conducted by Lambogia (2018) of workers at PT Tropica Cocoprima stated that more than half (50.7%) of workers had a work accident. The results of this study were also supported by Khairani in 2015 on the part of production workers who stated that the majority of workers had work accidents (71.7%) (Khairani, 2015;Winarto et al, 2016;Lombogia et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, a study conducted by Lambogia (2018) of workers at PT Tropica Cocoprima stated that more than half (50.7%) of workers had a work accident. The results of this study were also supported by Khairani in 2015 on the part of production workers who stated that the majority of workers had work accidents (71.7%) (Khairani, 2015;Winarto et al, 2016;Lombogia et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…The results of this study indicated that more than half of the workers have experienced work accidents. Study by Winarto et al (2016) of oil and gas seismic survey workers at PT X West Papua, stated that half of the sample (50%) had a work accident. In addition, a study conducted by Lambogia (2018) of workers at PT Tropica Cocoprima stated that more than half (50.7%) of workers had a work accident.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Martiwi, Koesyanto and Pawenang (2017) has also shown that the work environment has a significant effect on workplace accidents at PT Putri Midai. This is further supported by Winarto, Denny and Kurniawan (2016) suggesting that the condition of the work environment has a significant relationship with workplace accidents.…”
Section: Housekeeping Scopementioning
confidence: 56%
“…Dalam hal kecelakaan kerja disebabkan oleh manusia dengan perilaku kerja yang tidak aman (unsafe act), serta kondisi kerja (unsafe conditions) [6] [7]. Berdasarkan dari Work in Safety Environment menjelaskan 98% disebabkan oleh unsafe act dan selebihnya unsafe condition [8]. Perilaku pekerja mempunyai peran penting dalam keselamatan dan kesehatan kerja [9].…”
Section: Pendahuluanunclassified